Functional Liposomes Improve the Oral Absorption of Lurasidone Hydrochloride by Overcoming Multiple Absorption Barriers and Eliminating Food Effect - Song T; Wang W; Wu Y; Liu C; Yuan L; Sun Z; Zhang J; Sun Y (International Journal of Nanomedicine)
Tingting Song,1 Wenyu Wang,1 Yan Wu,2 Chaolong Liu,1 Lu Yuan,1 Zhihong Sun,1 Jingjing Zhang,1 Yong Sun1 1Department of Pharmaceutics, School of Pharmacy, Qingdao University, Qingdao, Shandong, 266071, People’s Republic of China; 2Department of Obstetrics and Gynecology, The Affiliated Qingdao Hiser Hospital of Qingdao University, Qingdao Hospital of Traditional Chinese Medicine, Qingdao, Shandong, 266033, People’s Republic of ChinaCorrespondence: Yong Sun, Department of Pharmaceutics, School of Pharmacy, Qingdao University, Qingdao, Shandong, 266071, People’s Republic of China, Email sunyong@qdu.edu.cnPurpose: Mental illness is the leading cause of the global burden of non-fatal disease. Lurasidone hydrochloride (LSD) is an important antipsychotic drug, but has poor water solubility and low oral bioavailability (9– 19%). Additionally, LSD exhibits twice the positive food effect, meaning that patients need to consume 350 kcal when taking the medication, which leads to reduced adherence. In this study, we developed oral LSD liposome enteric-coated capsules to eliminate the food effect and improve the oral bioavailability of LSD.Methodsc: Firstly, liposomes were prepared by cethanocl injection cmethod, and their morphology, particle size, polydispersity index, encapsulation efficiency, drug loading capacity, stability and in vitro release were characterized. Subsequently, the mucous permeability and transepithelial transport capacity of p-R8-DOCA-Lipos in intestinal epithelial cells were investigated, and the in vivo pharmacokinetics and biosafety of LSD liposome enteric-coated capsules were further studied.Results: p-R8-DOCA-Lipos had uniform morphology (particle size~112 nm), high encapsulation efficiency and drug loading capacity, and good stability in SIF. Cellular studies have shown that pHPMA gradually dissolved as it penetrated the mucus layer, and exposed R8-DOCA-Lipos facilitated cellular uptake. The cellular uptake and cumulative transepithelial transport of p-R8-DOCA-Lipos were 4.96 and 3.80 times higher than those in the solution group, respectively. The endocytosis of p-R8-DOCA-Lipos were mainly mediated by clathrin, caveolin and ASBT. Intracellular tracing showed that p-R8-DOCA-Lipos could achieve lysosomal escape, and ER and GA pathways were involved in their intracellular transport. In vivo pharmacokinetic studies have shown that AUC0-t of p-R8-DOCA-Lipos under fasted and fed conditions were similar to that of LSD suspension under fed conditions, which reduced the food effect of LSD and improved patient compliance. Finally, they had good biosafety after continuous oral administration.Conclusion: Therefore, p-R8-DOCA-Lipos may be a promising strategy for overcoming multiple gastrointestinal barriers to improve oral absorption of LSD. Keywords: oral delivery, liposomes, lurasidone hydrochloride, mucus permeation, transcytosis, bioavailability